2012
DOI: 10.1007/s11064-012-0766-5
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Glutamine Synthetase Inhibition in Epilepsy

Abstract: Glutamine synthetase (GS, E.C. 6.3.1.2) is a ubiquitous and highly compartmentalized enzyme that is critically involved in several metabolic pathways in the brain, including the glutamine-glutamate-GABA cycle and detoxification of ammonia. GS is normally localized to the cytoplasm of most astrocytes, with elevated concentrations of the enzyme being present in perivascular endfeet and in processes close to excitatory synapses. Interestingly, an increasing number of studies have indicated that the expression, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 137 publications
2
46
0
2
Order By: Relevance
“…Neuronal excitation involving the excitatory glutamate receptors is recognized as an important underlying mechanism in neurodegenerative disorders (Wang et al 2005). Several studies have indicated that the activity of GS in astrocytes is diminished in several brain disorders, including epilepsy (Eid et al, 2012). Earlier studies have shown the decreased activity and expression of GS in kainic acid induced epilepsy and it has been hypothesized that the loss of GS activity in epilepsy leads to increased extracellular glutamate concentrations and epileptic seizures (Swamy et al, 2011a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal excitation involving the excitatory glutamate receptors is recognized as an important underlying mechanism in neurodegenerative disorders (Wang et al 2005). Several studies have indicated that the activity of GS in astrocytes is diminished in several brain disorders, including epilepsy (Eid et al, 2012). Earlier studies have shown the decreased activity and expression of GS in kainic acid induced epilepsy and it has been hypothesized that the loss of GS activity in epilepsy leads to increased extracellular glutamate concentrations and epileptic seizures (Swamy et al, 2011a, b).…”
Section: Discussionmentioning
confidence: 99%
“…28,35 Thus, neurons are dependent on properly functioning astrocytes, and perturbations in astrocyte specific enzymes, including glutamine synthetase, have been described in many pathological conditions. [36][37][38] Glutamine synthetase is localized in astrocytic cytoplasm, and one of its main roles is to detoxify glutamate and ammonia by converting them into glutamine. The rate of glutamine synthesis can be directly determined by label incorporation into glutamine.…”
Section: Figmentioning
confidence: 99%
“…Note the metabolic relationship among astrocytes, GABAergic neurons, and glutamatergic neurons as indicated by the glutamine-glutamate-GABA cycle ( purple arrows to the left ) and the glutamine-glutamate cycle ( red arrows to the right ). ADP adenosine diphosphate, ASAT aspartate aminotransferase, ATP adenosine triphosphate, GABA c-aminobutyric acid, coA coenzyme A, GAT3 GABA transporter subtype 3, GAD65 / 67 glutamate decarboxylase isoforms 65/67, GDH glutamate dehydrogenase, MCTs monocarboxylate transporters, PAG phosphate-activated glutaminase, SAT1 / 2 system A transporter subtypes 1/2, SN1 system N transporter subtype 1, VGAT vesicular GABA transporter, VGLUT vesicular glutamate transporter (Adapted from [ 36 ] and reproduced with permission from Neurochem Res\Springer) glutamate transporters (VGLUT) [ 13 , 14 ]. After release from synaptic vesicles, glutamate binds to glutamate receptors in neurons and glial cells.…”
Section: Glutamine and Glutamine-glutamate-gaba Cyclementioning
confidence: 99%
“…The mechanism may be same as that in clinical seizures induced by fever in patients with febrile convulsions or epilepsy. The reason for the pronounced increase could result from the slow rates of glutamate-glutamine cycling, although the release of glutamate from astrocytes into extracellular space may also be involved [ 36 ]. By magnetic resonance spectroscopy, the epileptogenic, gliotic human hippocampus appears to be characterized metabolically by an increase in glutamate content, decreased glutamine content, and slow rates of glutamate-glutamine cycling [ 37 ].…”
Section: Glutamine/glutamine-glutamate-gaba Cycle and Epilepsymentioning
confidence: 99%
See 1 more Smart Citation